How to do everything with Office XP - Ulrich, Laurie Ann. (New York : Osborne McGraw-Hill, 2001)
Another release in our successful How to Do Everything series, this friendly, solutions-oriented book is filled with step-by-step examples for using the Office xp suite. Each chapter begins with the specific how-to topics that will be covered, and within the chapter, each topic is accompanied by a solid, easy-to-follow walkthrough of the process. The book covers all the programs in the suite, including Word, Excel, Access, Outlook, PowerPoint, and FrontPage. You'll also get details on the new features, such as speech and collaboration tools.
Part I: Office 2001 Common Elements. Chapter 1: Common Menu and Toolbar Features. Chapter 2: Working with the Clipboard. Chapter 3: Using Office Collaboration Tools. Chapter 4: Using the Media Gallery to Enhance Office Documents. Chapter 5: Office 2001 and the Web. Part II: Creating Documents with Word. Chapter 6: Building a Basic Document. Chapter 7: Effective Document Formatting. Chapter 8: Saving and Printing Documents. Chapter 9: Building Tabbed Lists. Chapter 10: Structuring Documents with Tables. Chapter 11: Creating a Newsletter with Columns. Chapter 12: Using the Drawing Canvas. Part III: Crunching Numbers and Keeping Lists with Excel. Chapter 13: Building a Workbook. Chapter 14: Working with Formulas and Functions. Chapter 15: Formatting a Worksheet. Chapter 16: Building and Maintaining List Databases. Chapter 17: Charting Excel Data. Chapter 18: Printing Worksheets. Part IV: Creating Presentations with PowerPoint. Chapter 19: Planning a Presentation. Chapter 20: Working with Presentation Text. Chapter 21: Adding Graphics, Sound, and Motion. Chapter 22: Displaying Data with Charts. Chapter 23: Setting Up Transitions and Animation. Chapter 24: Running an Effective Slideshow. Part V: Managing Data with Access. Chapter 25: Creating an Access Database. Chapter 26: Building Data Entry Forms. Chapter 27: Sorting & Querying Tables. Chapter 28: Generating Access Reports. Part VI: Keeping in Touch and on Schedule with Outlook. Chapter 29: Using the Outlook Inbox. Chapter 30: Scheduling with the Calendar. Chapter 31: Building a Contacts List. Chapter 32: Maintaining a Task List. Chapter 33: Using the Journal and Creating Notes. Part VII: Designing Web Pages with FrontPage. Chapter 34: Planning a Web Site. Chapter 35: Building Web Pages. Chapter 36: Posting Pages on the Web. Part VIII: Appendix. Working with Multiple Versions of Office.
Includes index.
Keywords: MICROSOFT OFFICE (COMPTUER FILE)